The unity of Plato's Gorgias : rhetoric, justice, and the philosophic life - Stauffer, Devin, 1970- (Cambridge University Press, 2006)
"This book brings out the complex unity of Plato's Gorgias. Through a careful analysis of the dialogue's three main sections, including Socrates' famous quarrel with Callicles, Devin Stauffer shows how the seemingly disparate themes of rhetoric, justice, and the philosophic life are woven together into a coherent whole. His interpretation of the Gorgias sheds new light on Plato's thought, showing that Plato and Socrates had a more favorable view of rhetoric than is usually supposed."--Jacket